The Effect Of Ethanol Extract Of Golden Sea Cucumber (Stichopus Hermanii) On Alt Levels In Aspirin-Induced Wistar Male Rats (Rattus Norvegicus) - Ferguszon, Devina Hanalily Maharani; Purwaningsari, Diah; Wienta Diarsvitri, Wienta; Poerwanto, Eka (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2025)
Drug-induced liver injury is the most common cause of acute liver failure in the United States. Hepatocyte injury can be caused by the consumption of high doses of aspirin, leading to the formation of free radicals. Golden sea cucumber (Stichopus hermanii) can play a role in prevention of free radicals through antioxidant. The study used a post test only control group design involving 32 wistar male rats divided into 4 groups : negative control (K-), positive control (K+), and two groups treated with Stichopus hermanii extract at doses of 486 mg/kg BB (KP1) and 972 mg/kg BB (KP2) for 23 days. The results of the study with Man-Whitney test showed that neither the groups treated with Stichopus hermanii extract at both doses of 486 mg/kg BB nor 972 mg/kg BB doses of Stichopus hermanii extract led to a significant reduction in ALT levels when compared to positive control. There was no significant difference in ALT levels between the two extract doses. The conclusion of this study is the administration of Stichopus hermanii extract at doses of 486 mg/kg BB dan 972 mg/kg BB for 23 days can not reduce ALT levels in aspirin-induced experimental animal.